The Limits to Dependent Growth in East-Central Europe - Martin Myant (Revue de la Régulation, 2018)
Between 1990 and 2017 the four central eastern European countries (CEECs), Czechia, Hungary, Poland and Slovakia narrowed the gap in economic levels with the EU average. The key driver in most of this period was inward foreign direct investment (FDI) by multinational companies (MNCs), which brought success for export-oriented manufacturing activities. This justifies a characterisation of the resulting variety of capitalism as “dependent”, following theories of dependent development used for Latin America. However, this development brought rapid growth only for a time, still leaving a substantial lag relative to western Europe. The potential for further growth is investigated with an analysis of the strategies pursued in CEECs by those MNCs, using data on the products they export. The fact of lower wages gives them good reasons for not transferring their most advanced products and processes to CEECs and the transfer of less advanced activities in turn helps keep wage levels below those of western Europe. The implication is that CEECs may not catch up with western Europe without a change in their growth model.